Basic education teachers in Brazil in one possible reading of educational policies - Souza, Angelo Ricardo; Gouveia, Andréa Barbosa (Education Policy Analysis Archives, 2011)
This article presents a reading of educational policies which have impact and/or relate to teachers’ work. Using data from Basic Education Assessment System (SAEB) and Brazilian National Education Census, this work builds a personal, professional and training profile of basic public education teachers in Brazil, and compares this profile with the demands for jobs in basic education and with the current national educational policies, so as to consider the challenges for public education in the country.